2017
DOI: 10.1007/s12094-017-1732-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of lymphocyte-to-monocyte, neutrophil-to-monocyte and neutrophil-to-lymphocyte ratios as prognostic markers in breast cancer patients treated with neoadjuvant chemotherapy

Abstract: High LMR and low NLR can be considered as favourable prognostic factors in BC patients treated with nCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 31 publications
5
73
5
Order By: Relevance
“…Studies including All BC Molecular Subtypes: DFS was the primary objective in six studies [23][24][25][26]28,29]. Only two (33%) found that a higher NLR was correlated with a shorter DFS in the univariate analysis [25,26].…”
Section: Results On Nlr and Dfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies including All BC Molecular Subtypes: DFS was the primary objective in six studies [23][24][25][26]28,29]. Only two (33%) found that a higher NLR was correlated with a shorter DFS in the univariate analysis [25,26].…”
Section: Results On Nlr and Dfsmentioning
confidence: 99%
“…(1) Patients Receiving Neo-Adjuvant Therapy Ten studies reported data on NLR as a predictive or prognostic factor in patients receiving neo-adjuvant therapy [22][23][24][25][26][27][28][29][30][31]. Among these studies, eight included patients with all molecular subtypes [22][23][24][25][26][27][28][29], one included only patients with triple negative BC (TNBC) [31] and the last one included only patients with hormone receptor-positive/HER2-negative BC [30]. The NLR cut-off for the statistical analyses was between 1.7 and 3.33, and was computed by a receiver operating characteristic (ROC) curve analysis in all studies.…”
Section: In Early Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potential epiphenomenon of chemotherapy-induced immunomodulation, we also studied NLR which has been reported to be associated with prognosis and response to chemothera- peutic agents in breast cancer in several studies [19][20][21][22]. In the present study, NLR was dynamically analyzed during eribulin treatment: at baseline, at best response and at progression.…”
Section: Discussionmentioning
confidence: 97%
“…37,38 Some studies have shown that inflammatory markers and immune-based prognostic indexes were used to evaluate the prognosis of breast cancer, such as NLR, d-NLR, MLR/LMR, and PLR. [39][40][41] However, these inflammatory markers were associated with poor prognosis in breast cancer patients, and the potential mechanisms were not yet clear. The SIRI based on three inflammatory cells, such as neutrophil, monocyte, and lymphocyte, and can fully evaluate the balance between host immune and inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%